The ACUSTILAB, a small Educational double reverberant chamber - António P. O. Carvalho (2002)
This paper presents the ACUSTILAB, an educational physical tool designed by the authors to be used by civil engineering students in laboratory classes regarding environmental and building acoustics. The ACUSTILAB is a fully functional scale model (about 1:2) of a double reverberant chamber with 1.5 x 3.5 x 1.4 m3. Its main use is to help teach the practical concepts of reverberation time and sound insulation and the effects of their variability by the visible use of different materials. This wheeled concrete model has its interior divided in two chambers by a movable separation that can be quickly changed according with the desired type of measurements. The upper enclosure simulates a slab to be used for structure borne transmission analysis. The ACUSTILAB is assisted by commercially available computer software to control the Reverberation Time, Dn.w (STC) and Ln,w (IIC) tests using a separate large screen to be visible by all the students surrounding the model during the classes.